RETRACTED: Navigating sustainability: The role of environmental accounting in enhancing business performance - Shatila Khodor; Nurzhaubayeva Raissa; Malishevskaya Natalia; Podolskaya Tatiana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001